Edible Plant Oil: Global Status, Health Issues, and Perspectives - Zhou, Ying; Zhao, Weiwei; Lai, Yong; Zhang, Baohong; Zhang, Dangquan (Frontiers in Plant Science, 2020)
Edible plant oil (EPO) is an indispensable nutritional resource for human health. Various cultivars of oil-bearing plants are grown worldwide, and the chemical compositions of different plant oils are diverse. The extremely complex components in oils lead to diverse standards for evaluating the quality and safety of different EPOs. The environment poses great challenges to the EPO safety and quality during the entire industrial chain, including plant cultivation, harvesting, oil processing, and storage. Environmental risk factors include heavy metal or pesticide residue pollution, insect or harmful microbial infestation, and rancidity. Here, the diverse components in oil and various oil-producing processes are discussed, including plant species, oil yield, and composition complexity, environmental factors that degrade oil quality. Additionally, we propose a whole-industrial-chain monitoring system instead of current single-link-monitoring approach by monitoring and tracking the quality and safety of EPOs during the entire process of plant cultivation, raw materials harvest, oil process, and EPOs storage. This will provide guidance for monitoring the quality and safety of EPOs, which were challenged by the deteriorating environment.